IMPROVING THE QUALITY OF GINING ON PRODUCTS - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The ginning process depends on many factors, among which the main ones are the characteristics of the processed cotton, the rotation speed of the saw, and the geometric dimensions of the saw tooth. It is impossible to determine the quality of the fiber by the arc of saw teeth engaged on it and the fiber separated around the seed comb. It can only be determined after passing beyond the grate.